2017
DOI: 10.5194/acp-17-11467-2017
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical properties of deposited airborne particulates over the Arabian Red Sea coastal plain

Abstract: Abstract. Mineral dust is the most abundant aerosol, having a profound impact on the global energy budget. This research continues our previous studies performed on surface soils in the Arabian Peninsula, focusing on the mineralogical, physical and chemical composition of dust deposits from the atmosphere at the Arabian Red Sea coast. For this purpose, aerosols deposited from the atmosphere are collected during 2015 at six sites on the campus of the King Abdullah University of Science and Technology (KAUST) si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 82 publications
1
24
0
Order By: Relevance
“…Owing to the negligible rainfall and minimal fluvial inputs of terrestrial material to the Red Sea and Gulf, desert dust deposition is believed to be one of the main sources of nutrients N, P and Fe to both marine environments (Acosta et al 2013). Engelbrecht et al (2017) reported that deposited desert dust for the same region of the Red Sea coastline as this study, contained on average 0.8% NO 3 − and 0.3% PO 4 3− . Assuming that 6 Mt and 5.5 Mt of mineral dust is deposited into the Red Sea and the Gulf every year, respectively (Hamza et al 2011, Jish Prakash et al 2015, which would be equivalent to ∼21 000 and ∼11 000 tonnes of N and P in both the Red Sea and the Gulf, we estimate that blue carbon habitats of Saudi Arabia could potentially accumulate between 0.3% and 0.8% of annually deposited nutrients by dust deposition.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Owing to the negligible rainfall and minimal fluvial inputs of terrestrial material to the Red Sea and Gulf, desert dust deposition is believed to be one of the main sources of nutrients N, P and Fe to both marine environments (Acosta et al 2013). Engelbrecht et al (2017) reported that deposited desert dust for the same region of the Red Sea coastline as this study, contained on average 0.8% NO 3 − and 0.3% PO 4 3− . Assuming that 6 Mt and 5.5 Mt of mineral dust is deposited into the Red Sea and the Gulf every year, respectively (Hamza et al 2011, Jish Prakash et al 2015, which would be equivalent to ∼21 000 and ∼11 000 tonnes of N and P in both the Red Sea and the Gulf, we estimate that blue carbon habitats of Saudi Arabia could potentially accumulate between 0.3% and 0.8% of annually deposited nutrients by dust deposition.…”
Section: Discussionsupporting
confidence: 63%
“…The sediments of the Red Sea and Arabian Gulf originate mainly from carbonate deposits from seawater and deposited airborne sediment of terrestrial origin, which is reported to comprise up to one-third of Gulf sediments (Sugden 1963, Saderne et al 2018. Dust deposition from frequent dust storms originating in the Sahara and the Arabian Peninsula is believed to be one of the primary sources of nutrients to the Red Sea and the Gulf (Acosta et al 2013, Engelbrecht et al 2017).…”
Section: Ecosystem Descriptionsmentioning
confidence: 99%
“…Additionally, it was observed that if a sandstorm and rainfall happen simultaneously, then the soiling rate is even greater as the accumulated sand adhered strongly to the panel surface, making the subsequent cleaning more difficult [14]. Further studies on soiling rate in Saudi Arabia, where the deposition of dust varies significantly between seasons from 5 g/m 2 /month (July) to 28 g/m 2 /month (August and October) [15], showed significant dust accumulation due to moisture and humidity, particularly from early-morning dews [12,16]. Other studies on the influence of wind velocity on dust accumulation found it to be insignificant [17].…”
mentioning
confidence: 99%
“…Comparison of Tokar Jet wind speed and the Indian Monsoon Index (Wang et al, 2001) from 2000-2009 shows significant correlations for monthly mean and August-only anomaly data ( Figure S1 in the supporting information; r = 0.91 and r = 0.52, p = 0.15, respectively (Zhai, 2011). The Tokar Jet generates dust storms originating from the Baraka River delta (Goudie, 2008;Hickey & Goudie, 2007; Figure 1), which can last for several days, depositing dust onto the Red Sea (Engelbrecht et al, 2017;Kalenderski & Stenchikov, 2016) and influencing surface water chemistry (e.g., Chen et al, 2008). The Tokar Jet generates dust storms originating from the Baraka River delta (Goudie, 2008;Hickey & Goudie, 2007; Figure 1), which can last for several days, depositing dust onto the Red Sea (Engelbrecht et al, 2017;Kalenderski & Stenchikov, 2016) and influencing surface water chemistry (e.g., Chen et al, 2008).…”
Section: 1029/2018gl081593mentioning
confidence: 99%
“…The Tokar Gap wind jet therefore represents a novel proxy for the overall intensity of the SAM circulation. The Tokar Jet generates dust storms originating from the Baraka River delta (Goudie, 2008;Hickey & Goudie, 2007; Figure 1), which can last for several days, depositing dust onto the Red Sea (Engelbrecht et al, 2017;Kalenderski & Stenchikov, 2016) and influencing surface water chemistry (e.g., Chen et al, 2008). A record of dust input to the south central Red Sea therefore has the potential to reconstruct long-term patterns of change in Tokar Gap winds and SAM intensity.…”
Section: Research Lettermentioning
confidence: 99%